Effects of Competition on the Profitability of Cement Manufactures in Kenya - Molonket, Lucy; Ombuki, Charles; Wawire, Nelson (My University, 2015)
The main objective of this study was to identify the effects of competition on the profitability of cement manufacturers in Kenya. This study adopted a survey research design while, stratified random sampling was used. Secondary and primary data collection methods specifically questionnaires and interviews were utilized in this study while both qualitative and quantitative research methods were also used. The study drew the sample of the study from the five cement companies operating in Nairobi Kenya. A response rate of 90% was achieved. The researcher found out that competition does impact on a company’s profitability either to some extent or to a great extent. Therefore, the researcher concluded that that for in terms of improving capacity of cement firms in Kenya in terms of countering competition, cement manufacturers should integrate innovation, quality service delivery, value chain adoption, integration of state of the art equipment, good financial management practices and constant re-evaluation in regard to profitability. This should also be realigned with the local realities in regard to Vision 2030, through establishing a regulatory authority, modernization of equipment, strong regional integration, proper infrastructure and regulation of the cement industry such that monopoly does not interfere with the industry. Keywords – Competition, Innovation, Modernization, Profitability and Value chain.